Pembinaan Peningkatan Literasi Keuangan Digital Bagi Ibu-Ibu Rumah Tangga - Hikmah, Hikmah; Efriyenti, Dian; Azmiana, Risca (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2025)
This community service aims to improve digital financial literacy for housewives, so that they can manage family finances more effectively and efficiently, and utilize digital technology to improve their economic welfare. Digital financial literacy includes an understanding of how to use technology to manage finances, such as online banking, e-wallets, and financial management applications. However, many housewives still have limited knowledge and skills in this area. This also happens to families who live in the Barelang Mega Jaya Sejati Housing Complex. The method used for this community service activity is the lecture and discussion method, so that a positive interactive dialogue occurs in order to produce several solutions to these problems. The results of this community service activity can have a positive impact on improving digital financial literacy for housewives.